Model Integrasi Perlindungan Perempuan Sebagai Saksi Dan Korban Kasus Kekerasan Seksual Yang Berbasis Komunitas - Nurcahyo, Edy; Mansyah, Muh Sutri; Sulayman, Sulayman (JURNAL USM LAW REVIEW, 2025)
The purpose of this research is to examine the model of protection for women as witnesses and victims in community-based sexual violence cases. This research is important considering the increasing number of sexual violence cases experienced by women, which further exacerbates and makes women more vulnerable. Sexual violence is a serious social issue, and the poor services for witnesses and victims to access legal protection have become a major problem. As experienced by witnesses and victims of sexual violence in South Buton Regency, the presence of witnesses and victims at the Police, Prosecutor's Office, and Court levels is often accompanied by parents or even alone. Thus, there is a potential for witnesses and victims to experience threats and violence, both psychologically and physically. This research method is a socio-legal research. The research results indicate that the protection of women as witnesses and victims of sexual violence cases is still not effective. This is due to law enforcement agencies not being aware of and not understanding the Sexual Violence Crime Act, as well as difficulties in interpreting the articles. As for the community-based protection model, the proposed concept is the Witness and Victim Community (SSK). The community is a partner of LPSK that serves as a solution in reaching and fulfilling the rights of women as witnesses and victims in South Buton.SSK's recommendations must be integrated into the criminal justice system. Tujuan penelitian ini untuk mengkaji model perlindungan perempuan sebagai saksi dan korban dalam kasus kekerasan seksual yang berbasi komunitas. penelitian ini penting mengingat  maraknya kasus kekerasan seksual yang dialami oleh perempuan, semakin memperburuk dan rentannya perempuan. Kekerasan seksual merupakan permasalahan sosial yang serius dan buruknya layanan saksi dan korban untuk mengakses perlindungan hukum, menjadi masalah utama. Seperti halnya yang dialami oleh saksi dan korban Kekerasan seksual di Kabupaten Buton Selatan, kehadiran saksi dan korban baik di tingkat Kepolisian, Kejaksaan, dan Pengadilan hanya didampingi oleh orangtua bahkan hanya sendirian saja. Sehingga berpotensi saksi dan korban mengalami ancaman dan kekerasan baik secara psikis maupun fisik. Metode penelitian ini merupakan penelitian socio-legal research. Hasil penelitian menunjukan perlindungan perempuan sebagai saksi dan korban kasus kekerasan seksual masih belum berjalan efektif, hal ini disebabkan oleh lembaga penegak hukum belum mengetahui dan belum memahami UU Tindak Pidana Kekerasan Seksual, selain itu kesulitan untuk menafsir pasal perpasal. Adapun model perlindungan berbasis komunitas, konsep yang diusulkan ialah Komunitas Saksi dan Korban  (SSK). Komunitas merupakan mitra LPSK yang menjadi solusi dalam menjangkau dan memenuhi hak-hak perempuan sebagai saksi dan korban di Buton Selatan. Saran SSK harus terintegrasi dalam sistem peradilan pidana.